ANTESEDEN KARIR DAN PENGARUHNYA TERHADAP KINERJA MANAJER BANK - Idayanti Nursyamsi (Jurnal Keuangan dan Perbankan, 2015)
Prior empirical reviews had suggested that several antecedent variables had an effect on banker's career and performance. In line with this we had built a conceptual model, developed a questionnaire, and used a multistage sampling method to collect responses from 102 bankers in Makassar, the capital city within the Provinces of South Sulawesi, Indonesia. Structural Equation Models showed that the antecedent variables (personality, organizational commitment, and human capital) had a significant effect on banker's career. Despite these positive findings, human capital had an insignificant positive relation to banker's performance. The relevance of these findings to prior empirical studies along with several recommendations to improve organizational effectiveness and future research had been given at the end of this paper.